2003
DOI: 10.1167/iovs.02-0679
|View full text |Cite
|
Sign up to set email alerts
|

Acute Radiolabeling of Retinoids in Eye Tissues of Normal andRpe65-Deficient Mice

Abstract: The results indicate preservation of a substantial inward flux of all-trans retinol from the circulation into the RPE of Rpe65(-/-) mice, despite the presence of abnormally high molar levels of RPE retinyl ester. They further imply the occurrence of a robust outward movement of all-trans retinol from the RPE into the circulation in Rpe65(+/+) mice, and substantial impairment of this efflux process in Rpe65(-/-) mice. These findings raise the hypothesis that in normal RPE, 11-cis retinal and/or 11-cis retinol s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 45 publications
3
38
0
Order By: Relevance
“…Because we now recognized unusual coactivator functions of Six3 upon rhodopsin transcription, we next investigated whether Six3 cooperates with previously characterized coactivators of rhodopsin promoter, such as NRL (24) and CRX1 (25). We found that Six3 is as effective as NRL or CRX1 in inducing transcription from the rhod-promoter reporter (Fig.…”
Section: Resultsmentioning
confidence: 87%
“…Because we now recognized unusual coactivator functions of Six3 upon rhodopsin transcription, we next investigated whether Six3 cooperates with previously characterized coactivators of rhodopsin promoter, such as NRL (24) and CRX1 (25). We found that Six3 is as effective as NRL or CRX1 in inducing transcription from the rhod-promoter reporter (Fig.…”
Section: Resultsmentioning
confidence: 87%
“…Elsewhere, we speculated that plasma lipoproteins taken up by RPE are stripped of nutrients required by photoreceptors (e.g., xanthophylls, cholesterol, vitamin E) and repackaged for secretion in BrM as large, EC-rich apoB-lipoproteins ( 24 ). Lipoprotein secretion by RPE cells could dispose of excess UC and forestall toxicity in concert with recycling of EC and retinoids ( 187 ) back to plasma. Within the RPE, apically-directed recycling of docosahexaenoate to the retina ( 124 ) may thus be accompanied by an independent, basally-directed recycling by guest, on April 29, 2019 www.jlr.org Downloaded from…”
Section: Discussionmentioning
confidence: 99%
“…A second possibility is that RPE65 is also involved in the mobilization of stored retinyl esters (43). The accumulation of retinyl esters is clearly dependent on LRAT activity (Figure 2), and these esters accumulate in Rpe65−/− mice.…”
Section: Accumulation Of All-trans-retinyl Esters In the Rpementioning
confidence: 99%
“…RPE65 was also proposed to be a retinyl esterbinding protein (27,44,45), hinting of its possible role in this process. Most insightful was the observation made by Pepperberg et al that, in normal RPE, there is a substantial exchange of all-trans-retinol with the blood circulation, whereas in Rpe65−/−mice, despite the presence of abnormally high molar levels of RPE retinyl esters, the outward movement is inhibited (43).…”
Section: Accumulation Of All-trans-retinyl Esters In the Rpementioning
confidence: 99%